Cardiac Structure-Function MRI in Patients After Heart Transplantation - Dolan, Ryan S. (J Magn Reson Imaging, 2018)
BACKGROUND: Following heart transplantation (Tx), recipients are closely monitored using endomyocardial biopsy, which is limited by cost and invasiveness, and echocardiography, which is limited regarding detailed structural and functional evaluation. PURPOSE: To test the feasibility of comprehensive structure-function cardiac MRI as a noninvasive modality to assess changes in myocardial structure and function. STUDY TYPE: Prospective. SUBJECTS: MR was performed in 61 heart transplant recipients (age 47.9 ± 16.3 years, 39% female) and 14 age-matched healthy controls (age 47.7 ± 16.7 years, 36% female). FIELD STRENGTH/SEQUENCE: 1.5T; 2D CINE steady state free precession (SSF)P imaging, T(2)-mapping, pre- and postgadolinium contrast T(1)-mapping, and tissue-phase mapping (TPM). ASSESSMENT: Quantification of myocardial T(2) (as a measure of edema), pre- and post-Gd T(1) (allowing calculation of extracellular volume (ECV) to estimate interstitial expansion), and TPM-based assessment of peak regional left ventricular (LV) velocities, dyssynchrony, and twist. STATISTICAL TESTS: Comparisons between transplant recipients and controls were performed using independent samples t-tests. Relationships between structural (T(2), T(1), ECV) and functional measures (myocardial velocities, dyssynchrony, twist) were assessed using Pearson correlation analysis. RESULTS: T(2) and T(1) were significantly elevated in transplant recipients compared to controls (global T(2): 50.5 ± 3.4 msec vs. 45.2 ± 2.3 msec, P < 0.01; global T(1): 1037.8 ± 48.0 msec vs. 993.8 ± 34.1 msec, P < 0.01). Systolic longitudinal function was impaired in transplant recipients compared to controls (reduced peak systolic longitudinal velocities, 2.9 ± 1.1 cm/s vs. 5.1 ± 1.2 cm/s, P < 0.01; elevated systolic longitudinal dyssynchrony, 60.2 ± 30.2 msec vs. 32.1 ± 25.1 msec, P < 0.01). Correlation analysis revealed a significant positive relationship between T(2) and ECV (r = 0.45,P < 0.01). In addition, peak systolic longitudinal velocities demonstrated a significant inverse relationship with T(2) (global r = −0.29, P = 0.02), and systolic radial dyssynchrony was positively associated with peak T(2) and peak T(1) (r = 0.26,P = 0.04; r = 0.27,P = 0.03). DATA CONCLUSION: MR techniques are sensitive to structural and functional differences in transplant recipients compared to controls. Structural (T(2), T(1)) and functional (peak myocardial velocities, dyssynchrony) measures were significantly associated, suggesting a structure-function relationship of cardiac abnormalities following heart transplant.